The impact of COVID-19 on primary retinopexy in preventing retinal detachment in a tertiary eye hospital emergency department. Issue 1 (January 2022) - Moussa, George; Samia-Aly, Emma; Andreatta, Walter; Lett, Kim Son; Mitra, Arijit; Sharma, Ash; Tyagi, Ajai K; Ch'ng, Soon Wai
Purpose: To review the effect of COVID-19 on rhegmatogenous retinal detachment (RRD) rate following primary retinopexy. Methods: Retrospective consecutive case series of 183 patients attending Birmingham and Midlands Eye Centre undergoing primary retinopexy (cryotherapy and laser) between March 23rd to June 30th in 2019 (Group 1) and 2020 (Group 2). Results: In total we reviewed 183 retinopexies, 122 in Group 1 and 61 in Group 2, a reduction of 50%. In Group 2 compared to Group 1, we showed a significant difference in characteristics of patients having primary retinopexy with an increase in proportion of male patients from 50 (41.0%) to 39 (63.9%) ( p  = 0.005), increase in high myopes from 1 (0.8%) to 4 (6.6%) ( p =  0.043), more slit lamp laser retinopexy from 83 (68.0%) to 52 (85.2%) ( p =  0.013) and less cryopexy from 21 (17.2%) to 2 (3.3%) ( p =  0.008). In Group 2, primary retinopexy resulted in significantly more 3-month RRD rate 1 (0.8%) to 5 (8.2%) ( p =  0.016). There were no changes in number of patients requiring further retinopexy ( p =  1.000) Conclusion: This study demonstrates a reduction of primary retinopexy, an increased risk for RRD following primary retinopexy and a significant shift in type of primary retinopexy performed, demographics, operator and change in characteristics of type of retinal break observed during this pandemic. This study contributes to the growing literature of the secondary effects of the COVID-19 pandemic on other aspects of healthcare that is not just limited to the virus itself.